2005
DOI: 10.1029/2004jd005631
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal variability of lightning activity over the Indian region

Abstract: [1] Spatio-temporal variability of lightning activity over the Indian land mass region (8°N-33°N, 73°E-86°E) has been studied using monthly satellite based lightning flash grid (5°Â 5°) data for 5-year (1998-2002) period. These data have been examined for depicting the annual, seasonal, and spatial distribution of the lightning activity. The study revealed the nonlinear relationship between lightning flash density and latitude on the annual timescale, and it is linked with the convective activity, large-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 43 publications
3
41
1
Order By: Relevance
“…Over AS, minimum activity is seen in July and August at 10°N. Slightly higher activity at 15°N in October and November months may be related to the convection developed by western disturbances (Kandalgaonkar et al, 2005). Over BoB, the activity starts from January and increases to attain maximum in the month of May at 10-11°N.…”
Section: Spatial Distribution Of Lightning Flash Density (Fd) Over Lamentioning
confidence: 98%
See 3 more Smart Citations
“…Over AS, minimum activity is seen in July and August at 10°N. Slightly higher activity at 15°N in October and November months may be related to the convection developed by western disturbances (Kandalgaonkar et al, 2005). Over BoB, the activity starts from January and increases to attain maximum in the month of May at 10-11°N.…”
Section: Spatial Distribution Of Lightning Flash Density (Fd) Over Lamentioning
confidence: 98%
“…These colder SSTs are not favourable for the development of the convection. Kandalgaonkar et al (2005) showed that the orography of the region is one of the factors controlling the convective activity and hence lightning activity. Thus, the observed higher FD along the eastern part AS may be attributed to the combined effect of orography, land-sea interaction and warmer SSTs.…”
Section: Spatial Distribution Of Lightning Flash Density (Fd) Over Lamentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the onset phase of the monsoon, the Indian land mass region experiences maximum convective instability caused by insolation [18] It is seen from Figure 6 that the negative LI is seen over March to September.…”
Section: The Frd Shows a Consistent Increase From February That Attaimentioning
confidence: 81%